2015
DOI: 10.1007/s11095-015-1643-0
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, Characterization, and Antitumor Properties of Trans- and Cis-Citral in the 4T1 Breast Cancer Xenograft Mouse Model

Abstract: Purpose Citral is composed of a random mixture of two geometric stereoisomers geranial (trans-citral) and neral (cis-citral) yet few studies have directly compared their in vivo antitumor properties. A micelle formulation was therefore developed. Methods Geranial and neral were synthesized. Commercially-purchased citral, geranial, and neral were formulated in PEG-b-PCL (block sizes of 5000:10000, Mw/Mn 1.26) micelles. In vitro degradation, drug release, cytotoxicity, flow cytometry, and western blot studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 29 publications
(37 reference statements)
0
38
0
1
Order By: Relevance
“…In these in vivo experiments, while there was significant reduction in tumor volume, even high doses of nanoparticles loaded with citral, neral or geranial did not cause noticeable toxicity in the animals57. Overall, all of these previous studies have suggested that citral and its constituents, neral and geranial, be considered as cytotoxic agents for the treatment of solid tumors.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…In these in vivo experiments, while there was significant reduction in tumor volume, even high doses of nanoparticles loaded with citral, neral or geranial did not cause noticeable toxicity in the animals57. Overall, all of these previous studies have suggested that citral and its constituents, neral and geranial, be considered as cytotoxic agents for the treatment of solid tumors.…”
mentioning
confidence: 63%
“…Recently7, we demonstrated that citral and its constituent isomers neral and geranial, when administered in a nanoparticle micelle formulation, caused significant decrease in growth of 4T1 tumors in autologous BALB/c mice. In this previous study, four injections of the monoterpene formulations were administered every third day after the tumors had attained a size of 50 mm 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations